2022
DOI: 10.3390/biomedicines10092185
|View full text |Cite
|
Sign up to set email alerts
|

J-Shaped Relationship of Serum Uric Acid with Unfavorable Short-Term Outcomes among Patients with Acute Ischemic Stroke

Abstract: (1) Background: The role of uric acid in stroke outcomes remains inconclusive. (2) Methods: We retrospectively enrolled 3370 patients with acute ischemic stroke. (3) Results: Uric acid level was higher in men than in women. Univariate analyses revealed that the rates of hyperuricemia were higher in all patients and in women for unfavorable outcomes. For death, the hyperuricemia rates were higher in all patients including men and women, and the uric acid levels were also higher in all patients and in women. A J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Others considered that too low or too high levels of uric acid both had a higher occurrence of ischemic stroke than moderate levels, which had the lowest incidence of ischemic stroke. 28 The association between ischemic stroke and uric acid was found to be positive, negative, U-shaped, or J-shaped, and there were also sex differences between them. However, studies reporting uric acid as a risk factor were more numerous than those reporting it as a protective factor.…”
Section: Discussionmentioning
confidence: 94%
“…Others considered that too low or too high levels of uric acid both had a higher occurrence of ischemic stroke than moderate levels, which had the lowest incidence of ischemic stroke. 28 The association between ischemic stroke and uric acid was found to be positive, negative, U-shaped, or J-shaped, and there were also sex differences between them. However, studies reporting uric acid as a risk factor were more numerous than those reporting it as a protective factor.…”
Section: Discussionmentioning
confidence: 94%
“…The mean serum uric acid levels of the patients were between 288.5 and 348.6 μmol/L. Outcome measures comprised functional outcome ( Lee et al, 2014 ; Zhang et al, 2016 ; Wang et al, 2018 ; Chen et al, 2020 ; Yuan et al, 2020 ; Bai et al, 2022 ; Liu et al, 2022a , b ), mortality ( Wang et al, 2018 ; Chen et al, 2020 ; Bai et al, 2022 ; Liu et al, 2022a ), hemorrhagic transformation ( Chen et al, 2020 ; Song et al, 2020 ; Cheng et al, 2022 ; Tian et al, 2022 ), symptomatic intracerebral hemorrhage ( Lee et al, 2014 ; Chen et al, 2020 ; Song et al, 2020 ; Yuan et al, 2020 ; Bai et al, 2022 ; Cheng et al, 2022 ), and post-stroke depression ( Gu et al, 2015 ; Li et al, 2020 ). Follow-up intervals ranged from 14 days to 12 months for functional outcome and mortality, 36 h to 7 days for hemorrhagic transformation, 24 h to 7 days for symptomatic intracerebral hemorrhage, and 9 days to 3 months for post-stroke depression.…”
Section: Resultsmentioning
confidence: 99%
“…This could be due to the potential nonlinear relationship between serum uric acid levels and functional outcome in acute ischemic stroke, resulting in an optimal node for serum uric acid levels. Some recent studies have added evidence to the associations of uric acid with functional outcome ( Bai et al, 2022 ; Liu et al, 2022a , b ), mortality ( Bai et al, 2022 ; Liu et al, 2022a ), hemorrhagic transformation ( Cheng et al, 2022 ; Tian et al, 2022 ), and symptomatic intracerebral hemorrhage ( Bai et al, 2022 ; Cheng et al, 2022 ). Thus, this dose–response meta-analysis of cohort studies aimed to update and clarify the shape of the relationship between serum uric acid levels and prognosis in patients with acute ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in the literature have shown that uric acid can have both positive and negative effects on the outcomes of AIS patients [27][28][29][30][31]. Liu et al [28] reported that extremely low or high uric acid levels have a negative effect on prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in the literature have shown that uric acid can have both positive and negative effects on the outcomes of AIS patients [27][28][29][30][31]. Liu et al [28] reported that extremely low or high uric acid levels have a negative effect on prognosis. In their study, they emphasized that low levels of uric acid (<4.1 mg/dL) may lead to adverse clinical outcome and death among men, while high levels of uric acid (>6.6 mg/dL) may predict death among women.…”
Section: Discussionmentioning
confidence: 99%